The Symptoms and Clinical events associated with Automatic Reprogramming (SCARE) at replacement notification study. Issue 12 (11th November 2018) - Sinha, Sunil K.; Carlson, Daniel; Chrispin, Jonathan; Barth, Andreas S.; Rickard, John Jack; Spragg, David D.; Berger, Ronald; Love, Charles; Calkins, Hugh; Tomaselli, Gordon F.; Marine, Joseph E.
Abstract: Background: Pacemaker patients experience battery depletion that activates pacemaker's alert for replacement notification. Automatic reprogramming at replacement notification can result in loss of rate response and atrioventricular (AV) synchrony. Objective: To determine if relevant symptoms or clinical events may be associated with automatic reprogramming at replacement notification. Methods: Electronic medical record review was undertaken for 298 patients referred for pacemaker generator replacement. Primary endpoints were symptoms or clinical events during replacement notification period. Results: Following elimination of duplicate pacemaker replacements ( n = 12), "near‐replacement notification" or "recalled" ( n = 15) and pacemakers at "end of life" ( n = 5), 266 subjects were included. Three distinct reprogramming cohorts were identified; those with no change ( control ) in pacing mode ( n = 46), those with loss of rate response ( n = 154), and those with loss of AV synchrony ± rate response ( n = 66). In total, 83 subjects (31.2%) had symptoms with significant differences seen between groups ( control = 4.3%, loss of rate response = 26.0%, loss of AV synchrony ± rate response = 62.1%, P < 0.001). Overall, 28 subjects (10.5%) experienced clinical events with significant differences seen between groups ( control = 0.0%, loss of rate response = 6.5%, loss of AV synchrony ± rate response = 27.3%, P < 0.001). Conclusions: Automatic reprogramming at replacement notification was associated with significant symptoms in 26% of those who lost rate response and in 62% of those who lost AV synchrony ± rate response . Additionally, 27% of the latter cohort required nonelective clinical care.